Fuzzy Model Reference Adaptive Controller for DC Motor - Mohammed Jasim, Wesam (Anbar Journal of Engineering Sciences, 2017)
In this work, a Fuzzy Model Reference Adaptive Controller FMRAC is presented for the speed control problem of a DC motor. The proposed controller is designed in two phases. In the first phase, the model reference input-output data is used to obtain the fuzzy rules. Then the effective rules are chosen to be used in the second phase. In the second phase, the obtained controller is applied in two conditions; the non fuzzy rules or adjusting the center of output membership functions. The simulation results shows a good speed motor tracking to the model reference in the word of the step response coefficients.